Pengaruh Faktor Sosial Terhadap Keputusan Pembelian Pada Toko Harapan Sukses Desa Sei Rakyat - Daslan Simanjuntak (Universitas Labuhanbatu, 2021)
Nowadays consumers are more selective in spending their money to buy products. Products that have good quality will be chosen by consumers. This causes the company to try even harder so that its products can be accepted by consumers, therefore it is very important for the company to know what is needed and desired by consumers of a product through consumer responses or responses so that the company benefits through consumer satisfaction that exceeds its expectations.Research so as not to lose direction in conducting research. The purpose of this study is to analyze the influence of social factors on purchasing decisions data collection is done by distributing questionnaires and distributed to consumers Toko Harapan Sukses Desa Sei Rakyat as many as 77 respondents. Data analysis in this study using the help of SPSS version 21. Data testing techniques conducted in this study include validity test, reliability, classical assumption Test, simple linear regression analysis partial testing and determinant coefficient. The results showed that the social factor variable t count value of 5.215 greater 1.906 significance level of 0.29< 0.5 and the coefficient of determinant value of R Square is equal to 0.375 or 37.5%, meaning the influence of promotion to the purchase decision of 37.5% while the rest is 62.5% is the influence of other factors.